Non-invasive brain stimulation for patient with autism: a systematic review and meta-analysis - Liu, Annan; Gong, Chao; Wang, Bobo; Sun, Jiaxing; Jiang, Zhimei (Frontiers in Psychiatry, 2023)
Objective To comprehensively evaluate the efficacy of non-invasive brain stimulation (NIBS) in patients with autism spectrum disorder (ASD) in randomized controlled trials (RCT), providing a reference for future research on the same topic. Methods Five databases were searched (Pubmed, Web of Science, Medline, Embase, and Cochrane library) and tracked relevant references, Meta-analysis was performed using RevMan 5.3 software. Results Twenty-two references (829 participants) were included. The results of the meta-analysis showed that NIBS had positive effects on repetitive and stereotypical behaviors, cognitive function, and executive function in autistic patients. Most of the included studies had a moderate to high risk of bias, Mainly because of the lack of blinding of subjects and assessors to treatment assignment, as well as the lack of continuous observation of treatment effects. Conclusion Available evidence supports an improvement in some aspects of NIBS in patients with ASD. However, due to the quality of the original studies and significant publication bias, this evidence must be treated with caution. Further large multicenter randomized double-blind controlled trials and appropriate follow-up observations are needed to further evaluate the specific efficacy of NIBS in patients with ASD.